Achieving successful EPR implementation with the penta-stage model. (28th January 2008) - Bali, Rajeev K; Wickramasinghe, Nilmini
Electronic patient record (EPR) systems are currently being implemented in a plethora of healthcare organisations on both sides of the Atlantic. These systems, through their ability to integrate several functions and provide seamless access to information, are expected to enable value-driven patient-centric healthcare delivery. At a time when healthcare globally is under tremendous pressure, EPR appears to be the panacea. However, EPR implementation has major organisational and cultural implications that to date have not been addressed and thus play a major role in the less than optimal results currently being experienced post EPR implementation. To address this issue, we discuss the need to incorporate the Penta-Stage model developed by analysing various EPR implementations in healthcare settings in both the UK and the USA.